Comparative analysis between education plans: Priorities in public policies for the stage of early childhood education at the national, state and three municipalities in the Greater ABC Region of São Paulo - Santos, Elisabete Filomena dos; Passone , Eric Ferdinando Kanai (Seven Editora, 2023)
The study described here is a comparative analysis of the National and State Education Plans and three municipalities in the Greater ABC Paulista Region, namely: Santo André, São Bernardo do Campo and São Caetano do Sul, referring to Goal 1, which deals with the stage of Early Childhood Education. This analysis allowed the unveiling of priorities evidenced by each instance (national, state and municipal) for the qualification of this educational stage. Such priorities are implied in a posteriori categories selected by the researchers, in order to enable the analysis of the goal and strategies through the technique of content analysis supported by Bardin (1977, 1994) and Franco (2008). This is a documentary research of mixed approach. Quantitative regarding the analysis of the categories found in each of the strategies of the highlighted plans and qualitative regarding the interpretation of these data through the interpretation of the researchers. As for the results found, it is observed that the main priority of the governors for this stage continues to be the issue of access to account for universalizing early childhood education in preschool for children from 4 (four) to 5 (five) years of age and expanding the offer of early childhood education in daycare centers for children up to 3 (three) years old. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-022